Comparative study of identity and cognitive characteristics from the perspective of sadra and cognitive psychology - Anbia Alimi; Sayed Asif Ehsani; Sayed Ahmad Ghafari (حکمت اسرا)
AbstractThe research aims to investigate cognition from the perspective of transcendental wisdom and cognitive psychology with a descriptive-analytical method and is an answer to the main question that "cognition in the Sadrai school and cognitive psychology, what identities and features are compatible or incompatible". Beyond the physical dimension of cognition, Sadra paid attention to other dimensions of human existence that are related to cognition, and by dividing cognition into presence and acquisition, he gave it an abstract dimension and argued. He proves the immunity of science and human knowledge. In cognitive psychology, only the physical dimension of cognition is mentioned, and this problem is analyzed from the physical method and paying attention to human experiential structures. Transcendental wisdom considers sense, heart, intellect, and the Qur'an to be the means of cognition, and the true knowledge of man is connected to revelation. Cognitive psychology considers the means of cognition to be only the five senses, which are related to the human nervous system. Consciousness, attention, language memory and decision-making are among the issues related to cognition. In the transcendental wisdom, imagination, while being a foundation for the creation of reason, is used in later stages as a tool to connect to the world of imagination, which has a dimension beyond the physical dimension; But in cognitive psychology, imagination is only a process of the nervous system to create images in the